Seasonal differences of Wyrtki Jet intraseasonal variabilities - Cao, Guojiao; Xu, Tengfei; Wei, Zexun (Frontiers in Marine Science, 2024)
This paper examines the intraseasonal variabilities (ISVs) of the Wyrtki Jet in boreal spring and fall and their impacts on the oceanic ISVs along the southern coast of Sumatra-Java Island. The results reveal that the Wyrtki Jet ISVs in spring are significantly stronger than those in fall, with the standard deviation of the 0-30m-averaged zonal current reaching up to 0.25 m/s in spring, while the highest value in fall is only 0.2 m/s. The Wyrtki Jet ISVs are significantly correlated with surface zonal wind anomalies and sea level anomalies (SLAs) in the equatorial Indian Ocean (EIO) at intraseasonal timescale, and are modulated by the propagation of equatorial Kelvin waves. The intraseasonal SLAs along the southern coast of the Sumatra-Java Island are significantly correlated with the Wyrtki Jet ISVs, exhibiting similar seasonal fluctuation characteristics. In spring, the Wyrtki Jet intraseasonal signals initially appear near 75°E at the equator, approximately 10 days before the positive peaks of the intraseasonal SLAs, while in fall, the Wyrtki Jet intraseasonal signals first appear about 15 days before the peaks near 60°E at the equator, which is relatively further west compared to signals in spring. In addition, the composite Wyrtki Jet ISVs in spring are approximately 0.2 m/s stronger than those in fall. The enhanced ISVs of sea surface zonal wind forcing and Wyrtki Jet in spring, relative to those in fall, indicate that the seasonality in the intraseasonal SLAs along the southern coast of Sumatra-Java is attributable to the combined effects of surface wind forcing and current fields.